Asymmetric electrocarboxylation of 4′-methylacetophenone over PrCoO3 perovskites. Issue 9 (30th March 2022) - Zhao, Yi-Jun; Yang, Li-Rong; Wang, Le-Ting; Wang, Ying; Lu, Jia-Xing; Wang, Huan
Abstract : Asymmetric electrocarboxylation of aromatic ketones has been achieved over PrCoO3 perovskites with the help of chiral auxiliary t -Bu( R, R )salen(Co[ii ]) under CO2 atmosphere. Abstract : PrCoO3 perovskites were synthesized by a traditional method followed by calcining at 500–900 °C, and were fully characterized using various scientific instruments. They were proposed as cathodes for the asymmetric electrocarboxylation of aromatic ketones with the help of the chiral auxiliary t -Bu( R, R )salen(Co[ii ]). A considerable yield (54%) and high enantiomeric excess (95% ee) of hydroxy acid were obtained. The good electrocatalytic performances were attributed to the contents of oxygen vacancies and Co 3+ active species of the PrCoO3 perovskites, which were affected by different calcination temperatures. Furthermore, PrCoO3 demonstrated high stability and reusability.